2020
DOI: 10.1515/rams-2020-0047
|View full text |Cite
|
Sign up to set email alerts
|

Study on microstructure and wear resistance of Zr-17Nb alloy irradiated by high current pulsed electron beam

Abstract: In this paper, the microstructure and wear resistance of Zr-17Nb alloy treated by high current pulsed electron beam were studied in detail. A phase change occurs after pulse treatments using X-Ray Diffraction (XRD) analysis, showing β (Nb) phase and α (Zr) phase transformed by a part of β (Zr, Nb) phase. Also, narrowing and shifting of β (Zr, Nb) diffraction peaks were found. Scanning Electron Microscope (SEM) and metallographic analysis results reveal that the microstructure of alloy surface before high curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Microstructure of the Zr-2.5Nb alloy observed by the SEM-EDX test was shown in Figure 2. Based on micro structure observation the grain of Zr-2.5Nb showed mainly equiaxed structure with relatively fine grain confirmed with the results of microstructure of the Zr-Nb alloys that revealed the increase of mechanical properties [13,14]. The main structure was relatively fine grain equiaxed structure that dispersed uniformly.…”
Section: Resultssupporting
confidence: 73%
“…Microstructure of the Zr-2.5Nb alloy observed by the SEM-EDX test was shown in Figure 2. Based on micro structure observation the grain of Zr-2.5Nb showed mainly equiaxed structure with relatively fine grain confirmed with the results of microstructure of the Zr-Nb alloys that revealed the increase of mechanical properties [13,14]. The main structure was relatively fine grain equiaxed structure that dispersed uniformly.…”
Section: Resultssupporting
confidence: 73%
“…High-current pulsed electron beam technology can solve the above problems. As a high-density energy source, HCPBE can achieve energy deposition on the material surface in a short time, irradiating the metal surface for rapid heating and cooling [11][12][13][14][15]. According to the literature, HCPEB treatment can refine the surface microstructure of metal, induce the melting of the aluminum matrix on the surface, fill the pores of the material and greatly improve the wear resistance, hardness and other properties [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, surface modification can achieve better surface quality, thereby increasing the service life of the material [13]. Recently, high-current pulsed electron beam technology (HCPEB), a surface modification micro-structure optimization technology, has attracted considerable attention because it is not affected by ion impurities, as ion beam technology is, and it has a much higher energy efficiency than the laser beam [14][15][16]. Ivanov et al used a highcurrent pulsed electron beam to process hypoeutectic Al-Si alloy and found that because of the presence of the submicron Al-based solid solution formed by HCPEB irradiation and nano-scale structure at the grain boundary, the hardness of the surface layer increased by 3.8-4.2 times [17].…”
Section: Introductionmentioning
confidence: 99%